The Relationship between TikTok and YouTube Use and Teaching Creativity of Economics Teachers in Pontianak City, Indonesia - Hasya Febrianty; Mashudi Mashudi; Husni Syahrudin; Maria Ulfah; Syamsuri Syamsuri; Hasya Febrianty; Mashudi; Husni Syahrudin; Maria Ulfah; Syamsuri (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2027)
The rise of video-based social media, particularly TikTok and YouTube, has opened new avenues for teachers to enhance their instructional creativity, yet empirical evidence within secondary-level economics education remains limited. This study examined the effect of TikTok application use and YouTube learning media on the teaching creativity of economics teachers in senior high schools across Pontianak City, both partially and simultaneously. A quantitative correlational survey design was employed. Data were collected through an online five-point Likert questionnaire from 423 students (214 female, 209 male) across seven senior high schools in Pontianak, capturing their perceptions of teachers' TikTok and YouTube use and teaching creativity. Data were analyzed using item validity and Cronbach's Alpha reliability testing, classical assumption tests, and multiple linear regression with heteroscedasticity-consistent (HC3) robust standard errors. Results indicated that TikTok use significantly and positively predicted teacher creativity (B = 0.332, p < .001), as did YouTube media use (B = 0.291, p < .001). Jointly, both variables explained 31.6% of the variance in teacher creativity (R2 = .316; F(2,420) = 30.33, p < .001). However, a pronounced ceiling effect in perception scores resulted in reliability coefficients below conventional thresholds (alpha = .49-.59), warranting cautious interpretation. This study contributes empirically to the Technological Pedagogical Content Knowledge (TPACK) literature by demonstrating that short-form and long-form video platforms complement, rather than substitute, one another in fostering teachers' pedagogical creativity in the digital era.